Mahkamah Konstitusi sebagai Benteng Hak Asasi dalam Sistem Pendididkan Nasional - Sahla Aulia; Muhammad Zenal Muttakin; Ramma Fawaz Abqari; Putri Ayu Salsabila (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to examine the role of the Constitutional Court (MK) in protecting and guaranteeing the right to education as part of human rights and the constitutional rights of Indonesian citizens.Education enshrined in Article 31 of the 1945 Constitution of the Republic of Indonesia is a fundamental right of every citizen that must be fulfilled by the state without discrimination.However, in its implementation, there are still gaps in access and violations of constitutional rights, especially for vulnerable groups and communities in marginalized areas. This research raises two main issues: (1) the gap in access and quality of education experienced by vulnerable groups and how the Constitutional Court protects those rights; and (2) violations of constitutional rights in the field of education.